Composite rock-breaking of high-pressure CO2 jet & polycrystalline-diamond-compact (PDC) cutter using a coupled SPH/FEM model - Cai, Can; Zhang, Pei; Xu, Daping; Yang, Xianpeng; Zhou, Yingfang (International journal of mining science and technology, 2022)
CO2 drilling is a promising underbalance drilling technology with great advantages, such as lower cutting force, intense cooling and excellent lubrication. However, in the underbalance drilling, the mechanism of the coupling CO2 jet and polycrystalline-diamond-compact (PDC) cutter are still unclear. Whereby, we established a coupled smoothed particle hydrodynamics/finite element method (SPH/FEM) model to simulate the composite rock-breaking of high-pressure CO2 jet & PDC cutter. Combined with the experimental research results, the mechanism of composite rock-breaking is studied from the perspectives of rock stress field, cutting force and jet field. The results show that the composite rock-breaking can effectively relieve the influence of vibration and shock on PDC cutter. Meanwhile, the high-pressure CO2 jet has a positive effect on carrying rock debris, which can effectively reduce the temperature rising and the thermal wear of the PDC cutter. In addition, the effects of CO2 jet parameters on composite rock-breaking were studied, such as jet impact velocity, nozzle diameter, jet injection angle and impact distance. The studies show that when the impact velocity of the CO2 jet is greater than 250 m/s, the CO2 jet could quickly break the rock. It is found that the optimal range of nozzle diameter is 1.5–2.5 mm, the best injection angle of CO2 jet is 60°, the optimal impact distance is 10 times the nozzle diameter. The above studies could provide theoretical supports and technical guidance for composite rock-breaking, which is useful for the CO2 underbalance drilling and drill bit design.